The case of smallholder dairying in Eastern Africa - Ngigi, Margaret (International Food Policy Research Institute, 2005)
Agriculture plays a crucial role in the economy of sub-Saharan Africa. A feature of particular significance about the region is that the majority of households are heavily dependent on agriculture as their major source of livelihood. Smallholder agriculture is the principal producer of staple foods and cash crops, accounting for very large shares of national production and marketed output. For the respective countries, therefore, the performance of smallholder agriculture has crucial implications for the overall economic development process including the alleviation of rural poverty. The demands created by steadily increasing populations, and the pressing need to increase agricultural productivity means that these countries must continuously adopt methods to intensify agricultural production.